The Prediction of Gender and Attachment Styles on Shame, Guilt, and Loneliness - (:unkn) unknown (EDAM, 2010)
The purpose of this study is to examine the predictive power of attachment styles and gender on negative social emotions such as shame, guilt, and loneliness. The sample consists of 360 (183 female, 177 male) students attending to different departments of Marmara University. The Relationships Questionnaire, Guilt-Shame Scale, and UCLA Loneliness Scale were used as instruments. Results obtained from hierarchical regression analysis showed that gender has a predictive power on shame, solely. When the predictivity of attachment styles on negative social emotions was examined, the results revealed that shame was predicted by secure and dismissing attachment style, whereas guilt was predicted by only dismissing attachment. Furthermore, all attachment styles played a determining role on loneliness.
Keywords: Attachment; Shame; Guilt; Loneliness; Negative Social Emotions; ADULT ATTACHMENT; SOCIAL-SKILLS; WORKING MODELS; SELF; VALIDITY; STUDENTS; SCALE